Inertia support during variable wind conditions - Persson, Mattias; Chen, Peiyuan; Carlson, Ola (2016 IEEE Electrical Power and Energy Conference (EPEC), 2016)
Wind variations are important to consider while designing inertia support strategies. A model has been evaluated but the findings should reflect issues with several control strategies utilizing a fixed inertia support pattern. Wind variability of 0.5 m/s from second to second is observed in real wind data. However, drastic changes in wind speed can occur within the duration of inertia support. An improved inertia control algorithm has been presented allowing a stable delivery of inertia support from variable speed wind turbines (VSWT) subjected to realistic wind conditions. The controller improves the previously presented inertia algorithm and smoothly transitions from a locked operation window to MPPT-operation. The impact of the utilized wind speed filter is described and its impact on the simulation found to be of great importance.